The Importance of Physical Activity in the Interaction of Motor and Cognitive Functions in Elderly People (Baltic Journal of Sport and Health Sciences, 2020)
Background. It is predicted that in 2060, the number of elderly people in Lithuania (62 and over years of age) will be 31.2% (Tamutienė & Naujanienė, 2013). The maintenance of stable posture requires particular attention because it gets more difficult to sustain it while doing multiple moves at the same time when you are getting older (Woo, Davids, Liukkonen, Chow, & Jaakkola, 2017). The aim of the study was to determine the importance of physical activity for the interplay of motor and cognitive functions in elderly people.Methods. Evaluation of static equilibrium by posturographic method, evaluation of cognitive functions, statistical analysis.Results. The results of the physically active and inactive research subjects were statistically significant (p = .043) in memory task with the eyes closed and in a simple position. A statistically significant difference in the sway velocity (Vsc) between the physical activity groups with eyes closed in simple position was also observed (p = .044). Double task with eyes closed resulted in worse balance performance.Conclusions. 1. Physical activity did not affect the motor function of the elderly. There were no differences between the physically active and inactive subjects in the assessed behavioral indices. 2. Physical activity did not affect the cognitive functions of the elderly. All elderly subjects were equally mistaken in their cognitive memory task. 3. The motor functions of the physically active elderly are controlled statistically significantly better when performing additional cognitive tasks than those of the physically inactive ones.Keywords: balance, elderly, physical activity.